300 m of U-Shaped Viaducts for Metro Lines From Around the World. Issue 2 (3rd April 2018) - Montens, Serge; Vollery, Jean-Charles; Pandey, Anand
Abstract: In the 1990s SYSTRA developed a patented, prestressed, concrete deck with a U-shape which has been adapted for use in metro viaducts. Two types of U-shape decks have been designed: the small-U and the big-U. This concept has many advantages in terms of concrete quantities, constructability, transportation system integration, environmental impacts and urban integration.